Pengaruh Pendapatan Asli Daerah, Dana Perimbangan Terhadap Pertumbuhan Ekonomi Dngan Belanja Modal Sebagai Variabel Intervening - Irvan, I Putu; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 3, Maret 2016 (pp.316 - 384), 2016)
Indonesia's economic development is highly dependent on local economic development. Fiscal decentralization give flexibility to local governments in regulating their regions and create policies that can support the potential in the region. The research objectives: 1) To analyze the influence of local revenues and equalization funds to economic growth, 2) To analyze the effect of local revenues and fund balance on economic growth through capital expenditures. This research was conducted in all districts / municipalities in the province of Bali. Data collection is done through the documents contained in the BPS. The data used in this research is secondary data of years 2007-2013, while the analytical technique used is the analysis of the path or path analysis. The analysis showed local revenues and equalization funds have a positive and significant direct effect on capital spending. The original income of the region and the balance funds have positive direct and significant effect on economic growth but capital spending has a direct effect of negative and not significant to the economic growth.
Keywords: Regional Income, Balance Fund, Capital Expenditures, Economic Growth